Formulation, Development, Characterization, and Cytotoxicity Study of Dasatinib Monohydrate Loaded Solid Self-Nano Emulsifying Drug Delivery System (SNEDDS) for Enhancement of Solubility and Oral Bioavailability: DAS-Loaded Solid SNEDDS for Enhanced Solubility and Bioavailability - Bavaskar, Kedar; Shaikh, Ashkan I.; Jain, Ashish S.; Morani, Dilip O.; Joshi, Shrikant (Iranian Journal of Pharmaceutical Sciences, 2026)
To improve the dissolution and solubility of dasatinib monohydrate (DAS), this study aimed to develop a solid self-nanoemulsifying drug delivery system (S-SNEDDS). Syloid 244FP was utilized as a solid carrier in this study to formulate and further develop liquid SNEDDS (L-SNEDDS) containing dasatinib monohydrate into a solid form. Based on the findings of the initial screening, nine batches of DAS-loaded SNEDDS were prepared using Tween 20, PEG 400, and Capryol 90 as surfactant, cosurfactant, and oil, respectively. Ternary phase diagrams were created for the chosen systems to determine the nanoemulsification region. The study demonstrates that the average globule size of the optimized batch of Self-Nanoemulsifying Drug Delivery Systems (SNEDDS) fell within the nanometric scale, with optimal Polydispersity Index (PDI) values. All batches also demonstrated rapid emulsification time, high drug loading efficiency, and good optical clarity. The development of uniform, spherical droplets smaller than 100 nm was demonstrated by TEM analysis. Over 90% of the DAS was released in about 120 minutes, according to in vitro DAS release from SNEDDS formulae. The optimized SNEDDS formulation was selected for conversion into solid SNEDDS (S-SNEDDS) using suitable solid carriers. The synthesized S-SNEDDS formulae were assessed for drug content, cytotoxicity, FTIR, in vitro dissolution, and micromeritic properties. It was discovered that S-SNEDDS formulations exhibited excellent flow characteristics, significant drug release, and elevated drug content. The MTT assay results indicate that DAS-S-SNEDDS exhibits a dose-dependent cytotoxic effect against the HL60 (Human Leukemia) cell line. Compared with standard cytotoxic agents, DAS-S-SNEDDS exhibits a significant, potent effect against the HL60 (Human Leukemia) cell line. In vitro drug release studies demonstrated a marked enhancement in the dissolution rate of DAS. These findings indicate that DAS-S-SNEDDS may serve as an effective strategy to enhance the oral bioavailability and solubility of DAS.